新冠肺炎重症患者ECMO治療的倫理考量: Ethical Considerations for ECMO Treatment of Patients with Severe COVID-19 - HAN, Dan (International Journal of Chinese & Comparative Philosophy of Medicine, 2022)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. ECMO是一項高風險、高創傷、高消耗的創新技術，它能夠為新冠病毒肺炎重症患者提供挽救性治療°ECMO的治療目標是幫助患者恢復心肺功能，或者橋接最終治療，包括器械植入，或者器官移植等。然而，容易被忽視的事實是，ECMO挽救了一些患者的生命，但也可能讓那些沒有康復機會的患者陷入醫療困境。於是，ECMO的臨床應用不得不面對一些反對意見，包括嚴重併發症危害患者生命安全、無效治療導致技術失敗，以及大量佔用資源損害醫療公平等。ECMO技術的臨床應用應該在尊重生命價值和患者意願的基礎上，合理設置治療目標、確立可接受退出標準、妥善處理患者意願與ECMO設備撤除困境之間的倫理衝突，建立適度倫理框架以合理控制醫療干預的邊界。 Characterized by high risk, high trauma and high consumption, Extra-Corporeal Membrane Oxygenation (ECMO) is an innovative technology that can be used as salvage therapy for COVID-19 patients. ECMO treatment can help restore patients' cardiopulmonary function or can bridge their final treatment, including device implantation or organ transplantation. However, although ECMO saves some patients' lives, it can also leave those with no chance of recovery in a medical dilemma. ECMO is thus controversial: it is criticized for technical failures and ineffective treatments, and its use raises questions about medical equity. This paper argues that the clinical application of ECMO technology should be based on a respect for the value of life and the will of patients, reasonably set therapeutic goals, acceptable withdrawal criteria, proper management of the conflict between patients' desires and the medical dilemma, and the establishment of an ethical framework to control the limits of medical intervention.